Mining and Analysis of SNP in Response to Salinity Stress in Upland Cotton (Gossypium hirsutum L.) - Wang, Xiaoge (PLoS One, 2016)
Salinity stress is a major abiotic factor that affects crop output, and as a pioneer crop in saline and alkaline land, salt tolerance study of cotton is particularly important. In our experiment, four salt-tolerance varieties with different salt tolerance indexes including CRI35 (65.04%), Kanghuanwei164 (56.19%), Zhong9807 (55.20%) and CRI44 (50.50%), as well as four salt-sensitive cotton varieties including Hengmian3 (48.21%), GK50 (40.20%), Xinyan96-48 (34.90%), ZhongS9612 (24.80%) were used as the materials. These materials were divided into salt-tolerant group (ST) and salt-sensitive group (SS). Illumina Cotton SNP 70K Chip was used to detect SNP in different cotton varieties. SNPv (SNP variation of the same seedling pre- and after- salt stress) in different varieties were screened; polymorphic SNP and SNPr (SNP related to salt tolerance) were obtained. Annotation and analysis of these SNPs showed that (1) the induction efficiency of salinity stress on SNPv of cotton materials with different salt tolerance index was different, in which the induction efficiency on salt-sensitive materials was significantly higher than that on salt-tolerant materials. The induction of salt stress on SNPv was obviously biased. (2) SNPv induced by salt stress may be related to the methylation changes under salt stress. (3) SNPr may influence salt tolerance of plants by affecting the expression of salt-tolerance related genes.